Analysis of 1x4 Power Combiner with Rectangular Slot for Microwave Application - Ali, N.S.A.S; Abd Aziz, M.Z.A.; Ahmad, B. H; Masrukin, Y. E.; Hussin, F. A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
This paper presents the design and analysis of the 1x4 Power Combiner with Rectangular Slot for Microwave Application. The focused frequency ranges were from 0.5 GHz to 6 GHz. Three main parameters were investigated in this paper which was length of slot (L1), width of slot (W1) and position of slot (distance). The numerical analysis had been done on the proposed parametric to characterize the effect. The design of tapered finline in the power combiner was simulated using a CST Microwave Studio Software. The simulation process was based on the input return loss and insertion loss at every input port. The rectangular slot was able to enhance the wideband by approximately 400 MHz. Index Terms—